2022
DOI: 10.3390/s22134742
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight Network for Point Cloud Analysis via the Fusion of Local Features and Distribution Characteristics

Abstract: Effectively integrating the local features and their spatial distribution information for more effective point cloud analysis is a subject that has been explored for a long time. Inspired by convolutional neural networks (CNNs), this paper studies the relationship between local features and their spatial characteristics and proposes a concise architecture to effectively integrate them instead of designing more sophisticated feature extraction modules. Different positions in the feature map of the 2D image corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…This improved fusion method slightly outperforms both PointNet & PointNet++ on the S3DIS dataset. Further variations of point cloud feature fusion methods can be found in publications by [110], [111] and [112] but going beyond exploring novel features computation or fusion, the work of [113] improved the fundamental network structure, which reduces processing power required and outperforms the current state-of-the-arts. Although this is a very active area of research, no research is found for use in the Cultural Heritage point cloud as an input or case study.…”
Section: Feature Fusion Methodsmentioning
confidence: 99%
“…This improved fusion method slightly outperforms both PointNet & PointNet++ on the S3DIS dataset. Further variations of point cloud feature fusion methods can be found in publications by [110], [111] and [112] but going beyond exploring novel features computation or fusion, the work of [113] improved the fundamental network structure, which reduces processing power required and outperforms the current state-of-the-arts. Although this is a very active area of research, no research is found for use in the Cultural Heritage point cloud as an input or case study.…”
Section: Feature Fusion Methodsmentioning
confidence: 99%